PECULIARITIES TRANSLATION OF CONCEPTUAL METAPHORS USED IN SELF-HELP DISCOURSE (E Conference Zone, 2022)
The article is devoted to the problem of translation of conceptual metaphors in poetic texts, as well as to the concepts of equivalence and adequacy of translations. The analysis of Uzbek translations of several cases of the implementation of metaphorical models «people are plants», life is a game” were carried out in the discourse of self-help. As a result of the study, it is concluded that adequate translation is important for the full transfer of the author's intention, worldview, and is also the basis for a successful dialogue between the cultures of the author and the reader.